Character Building and Good Habits for Students of SMK NU Rehobot, Kroya District, Indramayu Regency - Hasanudin; Dian Zahra N; Tasiroh; Putri Rahmah; Didik Himmawan (Aslama: Journal of Islamic Studies, 2024)
Juvenile delinquency today tends to increase along with various developments in technology and information that result in changes in values ​​in society. The existence of this juvenile delinquency makes society restless and worried about the future of these teenagers because teenagers are the next generation of the nation's ideals. The purpose of implementing the program is to instill character and good habits for students, SMK NU Rehobot with habits, namely praying duha as a congregational learning, continued with istigosah and joint prayer, praying together, and instilling character in students with religious sermons so that they are able to produce a generation of students who are intelligent, pious and have good morals. The delivery used is in the form of counseling to adolescent students at SMK NU Rehobot. This study uses a qualitative method. This study is a qualitative study that systematically describes the facts found in the field. The results of this study are good habits carried out by the entire school family, namely showing that the role of teachers is very important in preventing student delinquency and negative habits of students. Various factors from family and non-family contribute to bad habits of students, so strengthening the role of School Teachers is relevant in strategic diversion. Teachers have a crucial role in efforts to prevent and improve bad habits of students. Therefore, teacher empowerment and good habits of students continue to be carried out so that they can continue their education and have a better future for students of SMK NU Rehobot.